Enhancement of Anomalous Hall Effect via Interfacial Scattering in Metal‐Organic Semiconductor Fex(C60)1−x Granular Films Near the Metal‐Insulator Transition. (24th June 2019) - Zheng, Lingcheng; He, Zhihao; Zhang, Rui; Qu, Jiangtao; Feng, Deqiang; He, Jie; Chen, Hansheng; Yun, Fan; Cheng, Yahui; Li, Zhiqing; Liu, Hui; Zhang, Xixiang; et al.
Abstract: Ferromagnetic metal‐insulator granular films suffer from superparamagnetism, which causes a decrease in the values and temperature stabilities of the anomalous Hall effect (AHE). In this work, organic semiconductor (OSC) fullerene (C60 ), instead of the traditional inorganic insulators, is used as the matrix and a series of Fe x (C60 )1− x ( x = 0.58–0.91) granular films are fabricated. By utilizing the strong metal/OSC interfacial hybridization, the temperature stability of both magnetization and AHE is significantly improved, and the disordered scattering and consequently the anomalous Hall coefficient is enhanced. The saturated anomalous Hall resistivity of Fe0.58 (C60 )0.42 is 74 µΩ cm at 300 K, which is over three times larger than that of Fe0.59 (SiO2 )0.41 granular film, and it remains 63 µΩ cm at 2 K. The anomalous Hall coefficient of Fe0.58 (C60 )0.42 is 9.9 × 10 −8 Ω cm G −1, which is four orders larger than that of pure Fe and larger than most of the existing inorganic granular films. The roles of the intergrain Coulomb interaction, skew‐scattering, side‐jump, and intrinsic mechanism in AHE are evaluated. These results indicate that the organic materials have clear advantages in developing anomalous Hall devices. Abstract : Inorganic anomalous Hall effect (AHE) materials suffer from superparamagnetism when decreasing the device size to achieve high performance. Organic semiconductor C60 is utilized in the granular films for AHE devices. Benefitting from the unique property of C60, the anomalous Hall coefficient as well as the ferromagnetic stability is improved significantly.